From Classroom Projects to Formative Research: A Teaching Challenge in Higher Education - Penagos Cruz, Genaro (Rastros Rostros, 2015)
Purpose: this reflection article is part of a research project, which aims to assess and propose a working classroom tool that strengthens the research process in order to ensure motivation and appropriation of research topics for the establishment of research incubators in 2014.Description: research is based on the activation of previous knowledge and experiences in the classroom that create a cognitive structure, which facilitates a meaningful learning process in order to address a subject matter and further it.Point of view: teaching practice in the classroom was subject to assessment. This allows to evaluate the formative research process, by employing various monitoring and support strategies, in order to offer a wide response from the knowledge of specific issues that serve as a source to initiate an assertive research process. Thus, researchers are helped to objectively define a topic and a methodology that motivates them, strengthens communication among members, and promotes reflection on the subject matter.Conclusions: from study groups, a strategy that supplements the benefits that science and technology offer in the search for information emerges.
Keywords: research training; study groups; processes in the classroom